Physical activity and survival of colorectal cancer patients: population‐based study from Germany - Walter, Viola; Jansen, Lina; Knebel, Phillip; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann (International journal of cancer, 2017)
Increasing evidence shows physical activity to be associated with improved colorectal cancer (CRC) prognosis. However, large‐scale prospective patient cohorts, comprehensively ascertaining physical activity,...
Gesehen am 30.03.2017